2003
DOI: 10.1098/rspa.2003.1144
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anisotropic surface energy on the Rayleigh instability

Abstract: We determine the linear stability of a rod or wire subject to capillary forces arising from an anisotropic surface energy. The rod is assumed to be smooth with a uniform cross-section given by a two-dimensional equilibrium shape. The stability analysis is based on computing the sign of the second variation of the total energy, which is examined by solving an associated eigenvalue problem. The eigenproblem is a coupled pair of second-order ordinary di®erential equations with periodic coe±cients that depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This assumption is violated in many cases, concerning the effect of anisotropic surface energy. [ 14 ] The Rayleigh instability is commonly observed in metal nanowires. For example, Toimil-Molares et al reported the Rayleigh instability in copper nanowires annealed at temperatures between 400 and 600 ° C. [ 15 ] The copper nanowires fragment into chains of nanospheres, and the average diameter and spacing of the nanospheres second step is to thermally anneal the PMMA fi bers in ethylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…This assumption is violated in many cases, concerning the effect of anisotropic surface energy. [ 14 ] The Rayleigh instability is commonly observed in metal nanowires. For example, Toimil-Molares et al reported the Rayleigh instability in copper nanowires annealed at temperatures between 400 and 600 ° C. [ 15 ] The copper nanowires fragment into chains of nanospheres, and the average diameter and spacing of the nanospheres second step is to thermally anneal the PMMA fi bers in ethylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…The unit normal vector n at each particle on the symmetry plane must lie in the plane, i.e., m z ¼ 0 in Eq. (12). Thus, n at particle P 1 is calculated by fitting a circular arc through P 1 and two closest adjacent particles P 2 and P 3 on the plane.…”
Section: Computation Of Surface Curvature At the Symmetry Boundariesmentioning
confidence: 99%
“…The linear stability of free circular wires with isotropic surface energy, with respect to axial or circumferential perturbations was examined by Nichols and Mullins [30]. Surface energy anisotropy was factored in the linear stability analysis of free wires by Cahn [4] and Gurski and McFadden [12] (In a related study, Kan and Wong [16] considered the three-dimensional linear stability of a two-dimensional profile of a retracting edge of a film on a substrate (assuming isotropic surface energy) [15,8,43] and found one unstable mode of perturbation; thus the edge becomes wavy when perturbed. They determined the growth rate of the perturbation as a function of the wavelength of the perturbation and the speed of the receding edge).…”
mentioning
confidence: 99%
“…The thermal stability of nanomaterials is controlled by surface and diffusion processes and influenced by the material characteristics, temperature, and geometrical parameters [140144]. In particular, it was predicted that nanowires may fragment into a chain of nanospheres above a temperature that is much lower than the corresponding bulk melting temperature T m .…”
Section: Reviewmentioning
confidence: 99%